Malaria related myalgia-arthralgia: an imported case report treated with anti-malarial drug - Siagian, Forman E.; ., Ronny; Sirra, Apriani I.; Susiantoro, Urip; Siregar, Melsipa (International Journal of Basic & Clinical Pharmacology, 2020)
Malaria is still a major health problem in Indonesia, especially in endemic areas. We present an imported case of malaria with prominent subjective complaint of the patient is in the form of persistent muscles and joints pain. A 21 years old female with complaint of intermittent fever and persistent muscle joints paint since one week before seeing a doctor. She had history of repetitive attack of malaria tropica. Physical examination in general showed no clear derangements, but on thick and thin blood smear stained with Giemsa revealed malaria falciparum (+). Combo therapy of antimalarial drug soon be given and the patient healed with the disappearance of all previous complaint. Myalgia and arthralgia in case of malaria falciparum (+) might be the earliest subjective sign of rhabdomyolisis, a potentially fatal and lethal complication of malaria.